(untitled) (The Research of Medical Science Review, 2024)
Metal nanoparticles (MNPs) have emerged as powerful catalysts due to their high surface-area-to-volume ratio and unique electronic properties, enabling exceptional catalytic activity, selectivity, and stability. This review explores the mechanisms underlying catalysis by metal nanoparticles, highlighting their role in facilitating diverse chemical transformations. Key processes such as adsorption, activation of reactants, and intermediate formation are discussed to elucidate how MNPs enhance reaction kinetics. The applications of metal nanoparticles in catalytic processes are examined across various domains, including organic synthesis, environmental remediation, and industrial-scale production. Furthermore, challenges like nanoparticle aggregation, recyclability, and sustainability are addressed, alongside advancements in synthesis strategies and functionalization to improve catalytic performance. This comprehensive review aims to provide insights into the evolving field of metal nanoparticle-based catalysis, emphasizing their potential in addressing global scientific and industrial challenges.